PERANCANGAN SISTEM INFORMASI PROMOSI PADA PT.CENTERPOINT PUTRA SEJAHTERA BERBASIS SMS GATEWAY - Bobby Ghani; Nurfiana - (Jurnal Informatika, 2013)
The mobile application by using SMS (Short Message Service) is a service technology of messages delivery in short way. The user likes using SMS because of several reasons which are cheaper, more simple, and available in any kind of phone. PT. Centerpoint Putra Sejahtera is a retail company that has many costumers. The development of promotion information system with SMS Gateway base is made to simplify the costumer in getting the promotion information and point checking. This application is using Sekuensial Linear method that has analysis phase, design, codes and testing. The language program is using PHP, database saving is using MySQL, and Engine SMS Gateway use Gammu. The promotion information system will send SMS every time there is promotion which is happening or will happening in Centerpoint. The costumers also become easier to get point checking that has been collected while shopping in Centerpoint based on the SMS format. The result of testing system shows that the promotion information system based-on SMS Gateway can be used by the company.Keywords : SMS Gateway, Sekuensial Linier method, Promotion